2019
DOI: 10.1371/journal.pone.0212863
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analyses revealed differential strategies of roots and leaves from methyl jasmonate treatment Baphicacanthus cusia (Nees) Bremek and differentially expressed genes involved in tryptophan biosynthesis

Abstract: Baphicacanthus cusia (Nees) Bremek (B. cusia) is an effective herb for the treatment of acute promyelocytic leukemia and psoriasis in traditional Chinese medicine. Methyl jasmonate (MeJA) is a well-known signaling phytohormone that triggers gene expression in secondary metabolism. Currently, MeJA-mediated biosynthesis of indigo and indirubin in B. cusia is not well understood. In this study, we analyzed the content of indigo and indirubin in leaf and root tissues of B. cusia with high-performance liquid chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 56 publications
(54 reference statements)
2
11
0
Order By: Relevance
“…This study showed that MeJA could significantly improve F 0 , F m and F v /F 0 in Huangguogan and Shiranuhi at concentrations ≤2.2 mM, which was similar to results in soybean (Sirhindi et al 2016). However, 4.4 mM MeJA also inhibited the activity of the photosynthetic center, which was similar to the findings in Baphicacanthus cusia (Lin et al 2019).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This study showed that MeJA could significantly improve F 0 , F m and F v /F 0 in Huangguogan and Shiranuhi at concentrations ≤2.2 mM, which was similar to results in soybean (Sirhindi et al 2016). However, 4.4 mM MeJA also inhibited the activity of the photosynthetic center, which was similar to the findings in Baphicacanthus cusia (Lin et al 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Upon treatment with a low concentration of MeJA, the photosynthetic and transpiration rate in Huangguogan and Shiranuhi increased significantly, which was consistent with the results in cauliflower (Wu et al 2012). However, when the concentration of MeJA reached 4.4 mM, photosynthesis was significantly inhibited, similar to findings in Baphicacanthus cusia (Lin et al 2019) and S cutellaria baicalensis (Quan et al 2018). In addition, several other studies have shown that the photosynthetic rate of plants is dependent on the concentration of exogenous JAs in a non-linear fashion (Bali et al 2018, Agnihotri andSeth 2020).…”
Section: Role Of Jas In Increasing Photosynthetic Capacity and Chlorosupporting
confidence: 87%
See 1 more Smart Citation
“…Baphicacanthus cusia (Nees) Bremek is an herbal plant of the family Acanthaceae , mainly distributed in southern China, India and Myanmar. It is widely used as folk and clinical medicine [ 1 , 2 , 3 ]. The roots, stems and leaves of Baphicacanthus cusia can all be used as medicine and are commonly used in antiviral therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Since the SARS outbreak in 2003, interest in the antiviral properties of nanbanlangen has increased (Ni et al ., 2012), with particular recent attention being paid to the chemistry of S. cusia and the new indole alkaloids it contains (Lee et al ., 2019). Previous studies based on transcriptomic analysis revealed many candidate genes involved in the biosynthesis of indican backbone biosynthesis (Lin et al ., 2018, 2019).…”
Section: Introductionmentioning
confidence: 99%